A competição com plantas daninhas altera a morfologia, a bioquímica e o rendimento de grãos da soja - Rockenbach, Ana Paula (2018)
Soybean is the most economically important culture in the northern region of Rio Grande do Sul, its cultivation is subject to a series of weather changes, pests, diseases, and weeds. Among these, weeds compete with cultivation by light, water and nutrients. Considering this, the control of the species before the deployment of the crop is fundamental, thus, factors such as sequential application of desiccating herbicides and the use of residual herbicides in pre-emergence of culture are management strategies to assist in the total control of the species and of a new emergence flow in the initial stages. The lack of total control elevates the chances of plants resprouting in final and reproductive vegetation stages of soybeans, contemplated in this work as late competition. The general objective of this work was to verify the interference of residual action herbicides in the pre-emergence of soybean on the previous period to interference (PPI) and if there is interference of late competition of weeds in morphology, biochemistry, anatomy, grain yield, and components of soybean. For this reason, five field experiments and one greenhouse experiment were conducted at the University of Passo Fundo (UPF) in Passo Fundo/RS, and in commercial area in Chapada/RS during the period from October 2015 to April 2017. For the interference assessment of residual action herbicides in the pre-emergence of soybean on the PPI, two field experiments were conducted testing the herbicides diclosulam and flumioxazine on the cultivars NA 5909 RG and P 95R51. For the interference assessment of late weed competition in soybean, four field experiments and one greenhouse experiment were conducted, testing coexistence periods and densities between soybean and weed, where corn and horseweed (Conyza spp.) were used as weeds on morphological, biochemical and anatomical characters of root and aerial part, and on the yield and components of soybean. The use of the residual action herbicides diclosulam and flumioxazine increases the PPI on soybean cultivars NA 5909 RG and P 95R51 in infested areas mainly with horseweed and turnip. The emergence of the culture competition to the stage V6 affects the morphological characters of aerial and root part, and the biochemical constitution of soybean roots. The introduction of weeds in stages V3, V6 and R2 does not negatively alter the evaluated parameters. The anatomical constitution is not modified during the periods of coexistence with weeds. The corn that develops after the stage V4 of soybean, and resprouting horseweed plants during the cultivation do not negatively alter the secondary metabolism, the grain yield and the components of crop yield. The contents of the secondary metabolites, total phenols, flavonoids and saponins increase with horseweed density addition (Conyza spp.). The grain yield and components of total vegetable and grain yield are reduced when competing with different horseweed densities (Conyza spp.).